(untitled) (The International Journal for Scientific Research, 2026)
The present study aimed to investigate the effectiveness of an instructional program based on the visual approach in developing interdisciplinary thinking skills among sixth-grade students. The study employed a quasi-experimental design involving two equivalent groups: an experimental group and a control group. The research was conducted at Al-Khwarizmi School, affiliated with the Makkah Education Administration, during the 1447 AH academic year. The study sample consisted of sixth-grade elementary students who were randomly assigned to two groups. The experimental group studied the unit “Geometry: Angles and Polygons” through a specially designed program grounded in the visual approach, whereas the control group studied the same unit using conventional instructional methods. An interdisciplinary thinking skills scale was developed and validated for reliability and validity, then administered to both groups before and after the intervention. The findings revealed statistically significant differences at the level of (α ≤ 0.05) between the mean scores of the two groups on the post-test in favor of the experimental group. Based on these findings, the study recommended integrating visual-approach strategies into elementary mathematics curricula and providing teachers with professional training on their implementation to enhance interdisciplinary thinking skills and promote connections across multiple domains of knowledge.